Ethnobotany of Pohnpei : plants, people, and island culture - Balick, Michael J., 1952- (University of Hawaii Press : New York Botanical Garden, 2009)
"Ethnobotany of Pohnpei examines the relationship between plants, people, and traditional culture on Pohnpei, one of the four island members of the Federated States of Micronesia. Traditional culture is still very strong on Pohnpei and is biodiversity-dependent, relying on both its pristine habitats and managed landscapes; native and introduced plants and animals; and extraordinary marine life. This book is the result of a decade of research by a team of local people and international specialists carried out under the direction of the Mwoalen Wahu Ileilehn Pohnpei (Pohnpei Council of Traditional Leaders). It discusses the uses of the native and introduced plant species that have sustained human life on the island and its outlying atolls for generations, including Piper methysticum (locally known as sakau and recognized throughout the Pacific as kava), which is essential in defining cultural identity for Pohnpeians. The work also focuses on ethnomedicine, the traditional medical system used to address health conditions, and its associated beliefs."--Jacket